Lecturer-Student Collaboration in Higher Education as a Solution for Fostering Student’s Creative Personality - Aziz, Rahmat; Surur, Miftahus; Lestari, Sumia; Hotifah, Yuliati; Naim, Ngainun (FKIP Universitas Lampung, 2022)
Objective. This study aims to elaborate on the role of lecturer-student collaboration in developing student creativity. Method. This research is mix-method research. Data were obtained from 30 students and eight lecturers at three state universities in Malang, East Java. Data was collected through a creative personality scale and interviews. Quantitative data were analyzed using descriptive analysis techniques, while interview data were analyzed by thematic analysis. Findings. The analysis results show that lecturer-student collaboration activities have implications for the high level of student creativity. Conclusion. The results of this study have implications that lecturer activities have an essential role in developing student creativity. The limitation of this research lies in the data collection process, which is only done online. Further research is expected to use the method of observation and in-depth interviews to be able to reveal the data more comprehensively.Keywords: academic atmosphere, creativity, creative personality, lecturer-student collaboration, teaching models.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202219